On embedding degree sequences (Informatica, 2019)
Assume that we are given two graphic sequences, $π_1$ and $π_2$. We consider conditions for $π_1$ and $π_2$ which guarantee that there exists a simple graph $G_2$ realizing $π_2$ such that $G_2$ is the subgraph of any simple graph $G_1$ that realizes $π_1$.